Drug Resistance in Glioblastoma: The Two Faces of Oxidative Stress - Olivier, Christophe; Oliver, Lisa; Lalier, Lisenn; Vallette, François M. (Frontiers in Molecular Biosciences, 2021)
Glioblastomas (GBM) are the most common primary intra-cranial tumor, representing the major portion of malignant brain tumors, with a median survival of 15 months. A population of cells with stem cell properties (Glioblastoma stem cells, GSC) drives the initiation and progression of GBM and is localized in specialized microenvironments, which support their behavior. These are characterized by drug resistance and considered one of the determinants driving tumor relapse. Reactive oxygen species (ROS) control the cellular stability by influencing different signaling pathways. Normally REDOX systems prevent cell oxidative damage, however, in gliomagenesis the cellular REDOX mechanism are highly impaired. Here we review the dual nature of the REDOX status in drug resistance. ROS generation in tumor cells impact on the cell cycle and are involved in tumor progression and drug resistance in GBM. However, excess ROS production has been found to induce cell death programs such as apoptosis and autophagy. Since GBM cells have a high metabolic rate and produce high levels of ROS, metabolic adaptation in these cells play an essential role in resistance to oxidative stress-induced cell death. Finally, the microenvironment with the stromal components participates in the enhancement of the oxidative stress to promote tumor progression and drug resistance.